Information literacy as a guideline for development in Higher Education in the field of Medical Sciences - María Elinor Dulzaides Iglesias (Medisur)
Information literacy is a crucial guideline for development in Higher Education in the area of Medical Sciences. The analysis in this paper is based on the translation of the article "Understanding Information Literacy" by Barbara Humes and is aimed to achieve a higher degree of reflexion in university professors about this topic. In tis sense, some questions to help the understanding and involvement with the subject are stated, so that we can have competent professionals with a lifetime learning and a good quality as information consumers.